Characterization of Early EDEM1 Protein Maturation Events and Their Functional Implications - Tamura, Taku (American Society for Biochemistry and Molecular Biology, 2011)
The endoplasmic reticulum (ER) quality control factor EDEM1 associates with a number of ER proteins and ER-associated degradation (ERAD) substrates; however, an understanding of its role in ERAD is unclear. The early maturation events for EDEM1 including signal sequence cleavage and glycosylation were analyzed, and their relationship to the function of EDEM1 was determined. EDEM1 has five N-linked glycosylation sites with the most C-terminal site recognized poorly cotranslationally, resulting in the accumulation of EDEM1 containing four or five glycans. The fifth site was modified post-translationally when bypassed cotranslationally. Signal sequence cleavage of EDEM1 was found to be a slow and inefficient process. Signal sequence cleavage produced a soluble form of EDEM1 that efficiently associated with the oxidoreductase ERdj5 and most effectively accelerated the turnover of a soluble ERAD substrate. In contrast, a type-II membrane form of EDEM1 was generated when the signal sequence was uncleaved, creating an N-terminal transmembrane segment. The membrane form of EDEM1 efficiently associated with the ER membrane protein SEL1L and accelerated the turnover of a membrane-associated ERAD substrate. Together, these results demonstrated that signal sequence cleavage functionally regulated the association of EDEM1-soluble and membrane-integrated isoforms with distinct ERAD machinery and substrates.